2022
DOI: 10.7759/cureus.23975
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an Unscheduled Emergency Department Revisit Within 72 hours of Discharge

Abstract: Background An unscheduled emergency department (ED) revisit is defined as a patient presenting to the ED with the same problem within 72 hours of discharge. The revisits result in overcrowding and compromise the care provided by the ED. We assume that the poor quality of care provided by the ED is the reason for revisiting. However, the circumstances surrounding these revisits are not well-understood. We conducted this study to understand the characteristics associated with the revisits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…During the postimplementation phase, the rate of patients revisiting the ED with similar problems within 72 hours of discharge was reduced to <1%, which is considered an acceptable rate by some studies. Several factors influence whether a patient will revisit the ED, including age, sex, time and day of presentation, type of complaint, triage acuity level, physician expertise, investigations, treatment provided and hospital accessibility 27. By addressing these factors and implementing improvement strategies, the rate of revisits was successfully reduced in this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…During the postimplementation phase, the rate of patients revisiting the ED with similar problems within 72 hours of discharge was reduced to <1%, which is considered an acceptable rate by some studies. Several factors influence whether a patient will revisit the ED, including age, sex, time and day of presentation, type of complaint, triage acuity level, physician expertise, investigations, treatment provided and hospital accessibility 27. By addressing these factors and implementing improvement strategies, the rate of revisits was successfully reduced in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Several factors influence whether a patient will revisit the ED, including age, sex, time and day of presentation, type of complaint, triage acuity level, physician expertise, investigations, treatment provided and hospital accessibility. 27 By addressing these factors and implementing improvement strategies, the rate of revisits was successfully reduced in this study. Overcrowding in the ED is another concern, as it may lead to patients leaving the ED without being seen, which negatively affects patient satisfaction and compromises patient outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…11 However, some studies have suggested that illness-related factors are more common than patient-or healthcarerelated factors in causing return visits to the ED within 72 hours. 2,13 Physician-related return visits, which constitute one of the three categories of ED return visits within 72 hours alongside patient-related and illness-related returns, exhibit variable percentages based on available search results. 5 A study focused on a subset of return visits resulting in admission found that illness-related admissions accounted for nearly all admissions within 72 hours, while physician-related admissions accounted for only 3.5%.…”
Section: Discussionmentioning
confidence: 99%
“…19 Abdominal pain is the most common chief complaint in the first return visit, followed by cough and upper respiratory tract infection, with illness-related complaints being the most common reasons for revisits. 2,13 To minimize the need for patients to revisit the emergency department, healthcare providers need to ensure that patients are adequately prepared to manage their recovery at home and adhere to discharge instructions and prescription regimens. A study on general pediatric patients found that having access to a pediatrician reduced the likelihood of a return visit to the ED by nearly 30 percent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation